Windsock deformity of submitral left ventricular aneurysm communicating into left atrium – role of transesophageal echocardiography - Subash Sundar Singh; Vijay Thomas Cherian; Shaji Palangadan (Annals of Cardiac Anaesthesia, 2021)
Submitral left ventricular aneurysm (SMLA) is a rare condition. We report here a 38-year-old male patient, presented with mitral regurgitation and features of congestive cardiac failure (CCF) with New York Heart Association (NYHA) function class III, diagnosed to have SMLA. We discuss here the etiology, types, clinical presentation, and management of SMLA and also the role of transesophageal echocardiography in diagnosis.